Novel Coumarin–Pyridine Hybrids as Potent Multi-Target Directed Ligands Aiming at Symptoms of Alzheimer’s Disease - Babaei, Elaheh; Küçükkılınç, Tuba Tüylü; Jalili-Baleh, Leili; Nadri, Hamid; Öz, Esin; Forootanfar, Hamid; Hosseinzadeh, Elaheh; Akbari, Tayebeh; Ardestani, Mehdi Shafiee; Firoozpour, Loghman; Foroumadi, Alireza; Sharifzadeh, Mohammad; et al. (Frontiers in Chemistry, 2022)
In this research, a series of coumarin-based scaffold linked to pyridine derivatives via a flexible aliphatic linkage were synthesized and assessed as multifunctional anti-AD agents. All the compounds showed acceptable acetylcholinesterase (AChE) inhibition activity in nanomolar range (IC50 = 2-144 nM) and remarkable butyrylcholinesterase (BuChE) inhibition property (IC50 = 9-123 nM) compared to donepezil as the standard drug (IC50 = 14 and 275 nM, respectively). Compound 3f as the best AChE inhibitor (IC50 = 2 nM) showed acceptable BuChE inhibition activity (IC50 = 24 nM), 100 times more active than the standard drug. Compound 3f could also significantly protect PC12 and SH-SY5Y cells against H2O2-induced cell death and amyloid toxic effects, respectively, superior to the standard drugs. It could interestingly reduce β-amyloid self and AChE-induced aggregation, more potent than the standard drug. All the results suggest that compounds 3f could be considered as promising multi-target-directed ligand (MTDL) against AD.